2018
DOI: 10.1093/aje/kwy231
|View full text |Cite
|
Sign up to set email alerts
|

Social Isolation and Mortality in US Black and White Men and Women

Abstract: Social isolation is associated with higher mortality in studies comprising mostly white adults, yet associations among black adults are unclear. In this prospective cohort study, we evaluated whether associations of social isolation with allcause, cardiovascular disease, and cancer mortality differed by race and sex. Adults enrolled in Cancer Prevention Study II in 1982/1983 were followed for mortality through 2012 (n = 580,182). Sex-and race-specific multivariableadjusted hazard ratios and 95% confidence inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 39 publications
(57 reference statements)
3
91
1
1
Order By: Relevance
“…Among patients with coronary artery disease, male patients who are divorced or widowed show a poorer prognosis than married male patients (22,23). Furthermore, according to the Cancer Prevention Study-II report, among Caucasians, the HR for the all-cause mortality was higher in non-married men than in non-married women (24). However, there have been some reports showing that women are more sensitive and vulnerable to psychosocial stress, financial stress, or social isolation than men, which might affect the progression of HF and CVD (25-27).…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with coronary artery disease, male patients who are divorced or widowed show a poorer prognosis than married male patients (22,23). Furthermore, according to the Cancer Prevention Study-II report, among Caucasians, the HR for the all-cause mortality was higher in non-married men than in non-married women (24). However, there have been some reports showing that women are more sensitive and vulnerable to psychosocial stress, financial stress, or social isolation than men, which might affect the progression of HF and CVD (25-27).…”
Section: Discussionmentioning
confidence: 99%
“…25 An epidemiologic study amongst all races found a strong correlation between social isolation and all-cause mortality during a 30-year follow up period. 26 The theory underlying these repercussions are proposed to be from multiple etiologies.…”
Section: The Realitymentioning
confidence: 99%
“…It may also alter healthy behavioral practices with physical activity, sleep hygiene, and even medical adherence leading to overall poor outcomes. 26 In terms of COVID-19, it is crucial to understand that these social isolation and loneliness issues are the baseline for the older population. How additional social distancing recommendations will enhance social isolation and loneliness is still to be determined.…”
Section: The Realitymentioning
confidence: 99%
“…[1][2][3] Social isolation is consistently associated with poor health outcomes [4][5][6][7][8] and increased mortality. [9][10][11][12][13] Social isolation is particularly prevalent in older populations, affecting an estimated 17%-24% of older adults. 14,15 Although previous research 16 has shown that documented social and economic needs in the electronic health record are associated with future emergency department (ED) and hospital utilization, limited research has examined the specific effects of social isolation on health care utilization.…”
Section: Introductionmentioning
confidence: 99%